GIVING STUDENTS A BRIEF EXPLANATION ON ALTERNATIVE ENERGY SOURCES (Universal International Scientific Journal, 2026)
The Decree of the President of the Republic of Uzbekistan No. PF-4512 dated March 1, 2013 “On measures for the further development of alternative energy sources” states that “the conditions created in Uzbekistan for the practical use of solar energy and the existing opportunities serve as the basis for using this region as a pilot area for the introduction of advanced technologies in this area not only in our republic, but also throughout Central Asia,” and also emphasizes the presence of sufficient scientific and technical potential and experience in the use of alternative energy sources - solar, wind, and biogas in our republic [1].
Keywords: alternative energy, renewable resources, solar energy, wind energy, hydropower, biomass, geothermal energy, ecology, sustainable development